‘Evolution of Desire’ Review: Who Was René Girard? - Yalom, Marilyn (The Wall Street journal, 2018)
A comprehensive new biography on the life of a French intellectual of international prominence who crossed the boundaries of literature, history, psychology, sociology, anthropology and religion.